Pengembangan Media Puzzle pada Materi Iman kepada Allah Kelas II Madrasah Ibtidaiyah Pondok Pesantren Teknologi Darussalam Salu Induk - Kanna Rombe Allo, Sul Aisyah; Fakhrunnisaa, Nur; Thaha, Hisban (ISLAMIKA, 2025)
In order to gain insight into the development process, verification test outcomes, and practicality of using puzzle media in Islamic religious education, this study examines its impact on class II students' learning about faith in the Book of Allah at Madrasah Ibtidaya Pondok Pesantren Technologi Darussalam Salu Utama. Research Methodology The Dick and Carey Development Model used in R&D. Pondok Pesantren "Salu Induc Technology" an elementary madrasah with 18 students served as the site of the research. Questions, surveys, and records are all part of the data gathering process. The data was analyzed using both quantitative and qualitative descriptive methods. The results of the data analysis showed: 1) Using theDick and Carey development model, the development stage of Puzzle media was carried out. 2) The validation test yielded a percentage of 89.6% for media experts and 91.7% for material experts, putting it in the "very valid" category. 3) The practicalitytest yielded a percentage of 86.7% for student responses and an additional 87.5% for subject teachers, maintaining its "very practical" status. Therefore, the second graders at Darussalam Salu Induq Technology Islamic Boarding School have benefited much from creating Qur'an-based puzzle media.